Validation of local wisdom and culture as justification of cultural tolerance in Padang Sidempuan, North Sumatra - Harianto II; Teguh Satria Amin; Zulfitri Zulfitri (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This local wisdom is one of the products of tradition that lives in society and also develops in the environment of indigenous peoples which has been passed down from generation to generation. This local wisdom functions as a guide to behavior and also shapes people in life by displaying a wise, wise, kind and authoritative side that is firmly entrenched in people's lives and at the same time becomes a guide in that life. In today's society, sometimes local wisdom becomes one of the entities that determines human dignity, which presents intelligence, knowledge, and morals. This is one of the foundations of building a civilized society in the midst of the onslaught of the current era of globalization. This study uses a qualitative and ethnographic approach using primary data through interviews and documentation. This study found that local wisdom has validation that serves as justification for cultural tolerance in the Padang Sidempuan area. The powerlessness of indigenous peoples who are racing towards the traditional side is indeed threatened by the inability to maintain existence in order to continue the traditions of their ancestors which have begun to be eroded by the times.